PERANCANGAN SISTEM PRESENSI PESERTA KERJA PRAKTIK PADA KANTOR WILAYAH KEMENTRIAN AGAMA PROVINSI SUMATERA SELATAN - Nia Saka Lena; Muhamad Son Muarie (Jurnal Riset Sistem Informasi, 2026)
The internship attendance system at the Regional Office of the Ministry of Religious Affairs of South Sumatra Province still faces several issues, such as the potential for time manipulation, long queues due to a single QR code point, and inefficient attendance data recap procedures. The current process, which uses Google Spreadsheet, also cannot ensure alignment between the recorded attendance time and the participants’ actual physical arrival. To address these problems, this study designs a web-based attendance system that is more accurate, structured, and accessible without QR code scanning. This research applies a qualitative approach through field observation, interviews with responsible staff, and literature review. The system development adopts the Rapid Application Development (RAD) method, enabling quick iterations and active user involvement during the design phase. The results include a system design featuring account registration, check-in and check-out attendance, admin verification, attendance time settings, and automated real-time attendance reporting. This system is expected to enhance the effectiveness, accuracy, and efficiency of internship attendance management at the Regional Office of the Ministry of Religious Affairs of South Sumatra Province.